Evaluation of trimethoprim-sulfamethoxazole based combination therapy against Stenotrophomonas maltophilia: in vitro effects and clinical efficacy in cancer patients. (May 2017) - Araoka, Hideki; Baba, Masaru; Okada, Chikako; Abe, Masahiro; Kimura, Muneyoshi; Yoneyama, Akiko
Highlights: In vitro analysis was conducted on 89 S. maltophilia strains. 29 S. maltophilia bacteremia cases were reviewed. SXT + TIM had beneficial microbiological effects and was not antagonistic. Routine use of SXT + FQ combination is not recommended for S. maltophilia infection. Abstract: Objectives: The aim of this study was to evaluate the in vitro effects and clinical efficacies of trimethoprim-sulfamethoxazole (SXT) combined with other antimicrobial agents against Stenotrophomonas maltophilia . Methods: In vitro analysis was conducted on 89 S. maltophilia strains isolated from blood and the respiratory tract between June 2012 and October 2014. Levofloxacin (LVX), ticarcillin-clavulanic acid (TIM), and minocycline (MIN) were selected for an examination of their effects when individually combined with SXT by the checkerboard method. In addition, 29 S. maltophilia bacteremia cases were reviewed and the clinical efficacies of SXT-based combination therapies were analyzed. Results: SXT + LVX showed synergy in 21, no interactions in 61, and antagonism in 7. SXT + TIM showed synergy in 71, and no interactions in 18. SXT + MIN showed synergy in 10, and no interactions in 79. The review of clinical data indicated that a combination of SXT + fluoroquinolone was not associated with improved prognosis compared with monotherapy. Conclusions: The in vitro data indicated that SXT + TIM had beneficial microbiological effects and was not antagonistic. Our in vitro and clinical data analyses do not support the routine use of SXT + fluoroquinolone combination therapy for S. maltophilia infection.